Role of Entrepreneurial Orientation and Market Orientation to MSMES Performance - Sarah Nurlaeli Tanzil; Erry Sunarya; Dicky Jhoansyah (Almana : Jurnal Manajemen dan Bisnis, 2021)
The number of sales each year always decreases to the background in this study. The research aims to determine the influence of entrepreneurial orientation and market orientation on MSMEs performance. Methods used using a sampling method purposive distribute questionnaires for 32 respondents in the Wisata Kuliner Toserba Selamat Sukabumi. Analytical techniques use multiple linear regression analysis and hypothesis testing using partial tests and simultaneous testing. Result Determination (RSquare) 0.457 which means the effect of entrepreneurial orientation and market orientation for MSMEs performance 45.7% remaining amount of 54.3% is influenced by other variables. Based on the results of entrepreneurship orientation to the performance of UMKM reached Tcount 1,293 > Ttable 1.69, and the market orientation for UMKM performance shows the value of Tcount 2,304 > Ttable 1.69 means to have influence and significance. The result of the F-test has been done, the value of Fcount 12,227 > Ftable 3.33 means the orientation of entrepreneurship and market orientation positively and significantly towards MSMEs performance. means to have influence and significance.